Conocemos cómo se relacionan los seres vivos en el ecosistema - Rebaza Vera, Dany Del Rosario (2020)
The learning session entitled “We know how living beings related to the ecosystem” was developed in the area of science and technology. Taking into account the competence “Explaining the physical world based on knowledge about living beings, matter and energy, biodiversity, Earth and universe”. It was based on the necessary resource such as the ability to understand and use knowledge about living beings, matter and energy, biodiversity, Earth and universe, it has been possible to achieve in students the performance “Describing the interactions between living and non-living beings in their habitat. Example: The student points out that herbivores eat grass, that some animals feed on herbivores and that plants need the soil to live._x000D_ In the development of the learning session, motivating and challenging activities were applied which encourage children to describe and represent food chains and food webs; in addition, they reflected on the importance of conserving them, because if a change occurs that affects a living being of a certain chain, all the other members of this chain will be affected; which maintain the balance of ecosystems in our region or locality._x000D_ The pedagogical processes such as motivation and exploration of previous knowledge, problematization, construction of learning and information processing, assessment and transfer in the didactic processes of the area were taken into account._x000D_ The learning strategies were consistent with the interests and needs of students in third grade of primary education.